Future changes in extreme storm surges based on mega-ensemble projection using 60-km resolution atmospheric global circulation model. Issue 3 (3rd July 2019) - Mori, Nobuhito; Shimura, Tomoya; Yoshida, Kohei; Mizuta, Ryo; Okada, Yasuko; Fujita, Mikiko; Khujanazarov, Temur; Nakakita, Eiichi
ABSTRACT: This study examines long-term ensemble projections for historical and future climate conditions over 5, 000 years using an atmospheric global circulation model. The future climate condition is assumed as a constant +4K in the global mean temperature from before the Industrial Revolution (c.a. 1850), and the historical climate condition is perturbed by observed sea surface temperature (SST) error. A set of ensemble experiments assesses the impact of low probability phenomena, such as tropical cyclones and storm surge in comparison with conventional time-slice experiments. Future changes in storm surge will be severe at 15–35°N in the northern hemisphere, especially around the East Asia region. In addition, Future changes in regional storm surges targeting Tokyo and Osaka Bays project 0.3–0.45 m increase of storm surge height with a 100-year return period.